Silver nanoparticles prepared via an eco-friendly phytoextract method and their humidity sensing properties - M.V. Arularasu; M. Sai Deiv Ramkumar; Raghuraman Tarunprasad; Packirisamy Vinitha (Sensing and Bio-Sensing Research, 2025)
In this work, a resistive-type thin film humidity sensor is developed using phytoextracted silver nanoparticles (Ag NPs) for first time. Initially, Ag NPs were synthesized by a sustainable approach using the aqueous extract of turmeric powder, in which plant biomaterials function as both reducing as well as capping agents. The Ag NPs structural, morphological and composition properties were characterized using X-ray diffraction (XRD), X-ray photoelectron spectrum (XPS), Fourier transform infrared spectrum (FT-IR), UV–Visible, High resolution scanning electron microscopy (HR-SEM) coupled with energy dispersive X-ray (EDX) spectrometer techniques. The XRD result revealed a significant diffraction peak appeared at 38.62°, 44.16°, 66.29°, 76.53° which correspondent to the (111), (200), (220) and (311) plane would confirm the crystalline nature with cubic phase structure of Ag NPs. The spherical shaped morphological nature has been confirmed by HR-SEM analysis. The UV–Visible spectra showing a characteristic peak of Ag NPs at an absorption maximum at 429 nm. The humidity sensing properties of Ag NPs have been exposed to a humidity range from 5 % to 98 % relative humidity (RH) and three different testing frequency (100, 500 and 1000 Hz). The obtained results confirmed that the optimum testing frequency is 500 Hz. Consequently, we observed fast response (28 s) and recovery (47 s), low hysteresis characteristic, and long-term stability (up to 30 days). Owing to this merit, the implemented sensor has been illustrated for a great application prospect in smart food packaging, breath analysis, non-contact sensing, and soil monitoring.